Integrating Management Practices to Decrease Deoxynivalenol Contamination in Soft Red Winter Wheat - Rod, Katherine S.; Bradley, Carl A.; Van Sanford, David A.; Knott, Carrie A. (Frontiers in Plant Science, 2020)
Fusarium graminearum, the major causal agent of Fusarium head blight (FHB) of wheat (Triticum aestivum) in the U.S., can produce mycotoxins, such as deoxynivalenol (DON), during infection. Contamination of wheat grain with DON is a major concern for wheat producers and millers, and the U.S. Food and Drug Administration (FDA) has set advisory levels for DON in finished wheat products for human and animal consumption. Practices utilized to manage FHB and DON contamination include planting wheat cultivars with moderate resistance to FHB and applying efficacious fungicides at the beginning of anthesis. Under severe epidemics, DON contamination can exceed FDA advisory levels despite implementation of these measures. Additionally, fungicide efficacy can be limited when anthesis is not uniform among plants in the field, which can occur when planting is delayed or if there is non-uniform seedling establishment. The objectives of this study were to evaluate the effect of 1) in-furrow phosphorus application at planting and seeding rate on heading and anthesis uniformity, FHB symptomology, DON contamination, grain yield, yield components, and test weight; and 2) harvesting at different grain moisture concentrations on FHB symptomology, DON contamination, grain yield and test weight. Field trials were established in Princeton, Kentucky, from 2017 to 2019, to evaluate in-furrow phosphorus application at planting (0 kg P2O5 ha-1 and 47 kg P2O5 ha-1); seeding rate (376 live seeds m-2 and 603 live seeds m-2); and grain moisture at harvest (20 to 22% and 13 to 15%). In-furrow phosphorus increased grain yield and spikes m-2, but had no effect on heading and anthesis uniformity or DON contamination. The 603 live seeds m-2 seeding rate decreased the number of days to Zadoks 60 for the November planted wheat, and decreased FHB incidence, but did not decrease DON contamination. Harvesting at 20 to 22% grain moisture decreased Fusarium damaged kernel ratings and percent kernel infection but increased DON contamination in the harvested grain. Although in-furrow phosphorus, seeding rate, and harvesting 20 to 22% grain moisture did not decrease DON contamination, there is potential for these treatments to alleviate negative effects of late planted wheat grown in stressful environments.